HUBUNGAN ANTARA KESEDIAAN PEMBELAJARAN ARAHAN KENDIRI DALAM PENDIDIKAN BERASASKAN HASIL/ OUTCOME BASED EDUCATION (OBE) DENGAN PENCAPAIAN AKADEMIK - Amiruddin, Mohd Hasril; Zulkepli, Nur Azuana; Rohanai, Reyan Healme (Online Journal for TVET Practitioners, 2018)
Self-learning strategy refers to the process of metacognition, a situation in which the students study their thought processes, assess performance and plan other alternatives to succeed. Lecturers develop independent learning strategies among students through teaching and learning strategies in order to meet the objectives of Outcome Based Education (OBE). Outcome Based Education is a system used at the Institute of Higher Education in Malaysia nowadays. It is a student-cantered approach that focuses on student learning. The purpose of this study was to determine the level of self-learning strategies, relationship of self-learning strategies with academic achievement and differences of self-learning strategies based on gender and program of study among Universiti Tun Hussein Onn Malaysia’ (UTHM) students . Selected respondent population was about 1846 students and randomly selected sample based on Krecjie Morgan schedule involving 346 people. Data was collected using questionnaires and analysed by using Statistical Package for the Social Sciences Version 18.0 (SPSS) to find frequency, the average mean, correlation and significant differences. The result of analyse the level of self-learning strategies are at the medium level, while the correlation of independent learning strategies and academic achievement was at r = -0195 and p = 0.00 where there is inverse correlation between the two variables. Further results of the Independent T test and ANOVA showed no significant difference between the level of independent learning strategies by gender and program of study. As proposed, the lecturers are expected to intensify efforts to implement the strategy of independent learning in students in order to achieve the goal of implementation of OBE.